Human Capital Development of Orang Asli Youth: Supportive and Suppressive Factors - Mustapha, Ramlee; Omar, Mustaffa; Syed Hassan, Syed Najmuddin; Mohd Yasin, Ruhizan; Mohd Salleh, Norani (Elsevier, 2010)
The aim of the research was to explore the factors that influence the human capital development of Orang Asli youth in Peninsular Malaysia. Surveys and interviews were conducted at Orang Asli settlements in Bera, Gua Musang, Cameron Highlands and Pulau Carey. High dropouts among Orang Asli students have become an issue as it was reported nearly 34% of those who had completed their primary schooling did not continue their studies at the secondary level. This article presents the supportive and suppressive factors that influence the human capital development among th Orang Asli youth.